Microencapsulation of probiotics using sodium alginate - Etchepare,Mariana de Araújo (2015)
The consumption of probiotics is constantly growing due to the numerous benefits conferred on the health of consumers. In this context, Microencapsulation is a technology that favors the viability of probiotic cultures in food products, mainly by the properties of protection against adverse environmental conditions and controlled release. Currently there are different procedures for microencapsulation using polymers of various types of natural and synthetic origin. The use of sodium alginate polymers is one of the largest potential application in the encapsulation of probiotics because of their versatility, biocompatibility and toxicity exemption. The aim of this review is to present viable encapsulation techniques of probiotics with alginate, emphasizing the internal ionic gelation and external ionic gelation, with the possibility of applying, as well as promising for improving these techniques.